Non-surgical treatment of knee osteoarthritis - Picado-Brenes, Daniel (2023)
Knee osteoarthritis is an increasingly common degenerative disease in modern society, directly associated with advanced age and obesity. Although its pathophysiology is not fully defined, several studies have shown that lifestyle changes, such as regular exercise and maintaining a healthy weight, can improve symptoms and slow down disease progression. This review article explores different non-surgical treatment options for knee osteoarthritis, emphasizing that topical and oral NSAIDs have the strongest evidence in both short and long-term outcomes. Opioids, due to their risks and limited long-term benefits, arediminishing in their role in managing this condition. Moreover, acetaminophen has been widely proven ineffective in treating knee osteoarthritis. Additionally, new techniques such as intra-articular substance injections are being investigated, offering potential additional therapeutic options. Overall, new discoveries and advancements in the treatment of this condition are expected in the future.